Visuomotor Activation of Inhibition-Processing in Pediatric Obsessive Compulsive Disorder: A Magnetoencephalography Study - Nishat, Eman; Dockstader, Colleen; Wheeler, Anne L.; Tan, Thomas; Anderson, John A. E.; Mendlowitz, Sandra; Mabbott, Donald J.; Arnold, Paul D.; Ameis, Stephanie H. (Frontiers in Psychiatry, 2021)
Background: Response inhibition engages the cortico-striato-thalamo-cortical (CSTC) circuit, which has been implicated in children and youth with obsessive compulsive disorder (OCD). This study explored whether CSTC engagement during response inhibition, measured using magnetoencephalography (MEG), differed in a sample of medication-naïve youth with OCD, compared to typically developing controls (TDC). Methods: Data was analyzed in 17 medication-naïve children and youth with OCD (11.7 ± 2.2 SD years) and 13 TDC (12.6 ± 2.2 SD years). MEG was used to localize and characterize neural activity during a Go/No-Go task. Task performance on Go/No-Go conditions and regional differences in amplitude of activity during Go and No-Go condition between OCD versus TDC were examined using two-sample t-tests. Post-hoc analysis with Bayesian t-tests was used to estimate the certainty of outcomes. Results: No differences in Go/No-Go performance were found between OCD and TDC groups. In response to the visual cue presented during the Go condition, participants with OCD showed significantly increased amplitude of activity in the primary motor (MI) cortex compared to TDC. In addition, significantly reduced amplitude of PCu was found following successful stopping to No-Go cues in OCD versus TDC during No-Go task performance. Bayesian t-tests indicated high probability and large effect sizes for the differences in MI and PCu amplitude found between groups. Conclusion: Our preliminary study in a small medication-naïve sample extends previous work indicating intact response inhibition in pediatric OCD. While altered neural response in the current study was found during response inhibition performance in OCD, differences localized to regions outside of the CSTC. Our findings suggest that additional imaging research in medication-naïve samples is needed to clarify regional differences associated with OCD versus influenced by medication effects, and suggest that MEG may be sensitive to detecting such differences.